STIMULASI GANGGUAN ARTIKULASI ANAK USIA 3 - 4 TAHUN MELALUI GERAK DAN LAGU TUJUH KEBIASAAN ANAK INDONESIA HEBAT DI PAUD ANAK KITA PRESCHOOL - Heppy Liana; Alyani Noor Septalia; Noor Lintang Bhaskara; Hasbi Sjamsir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Articulation disorders are among the most common language development disorders in early childhood and may hinder children's communication skills, social interaction, and self-confidence. This study aimed to describe the implementation of articulation disorder stimulation through the Movement and Song of the Seven Habits of Great Indonesian Children and to identify the supporting and inhibiting factors affecting its implementation at Anak Kita Preschool, Samarinda. This study employed a qualitative approach using a case study design. The participants consisted of five children aged 3–4 years with articulation disorders and three teachers serving as key informants. Data were collected through observation, semi-structured interviews, and documentation. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source and technique triangulation. The findings revealed that articulation stimulation was implemented systematically through four stages: introduction, movement and song activities, repetition of target phonemes, and evaluation of children's progress. The song lyrics contained repeated dominant phonemes, including the vowels /a/, /i/, and /u/, and the consonants /b/, /m/, /t/, /k/, /n/, /r/, and /s/, with particular emphasis on the phonemes /r/, /s/, /k/, and /g/, which are commonly mispronounced by children aged 3–4 years. Repetitive singing combined with body movements helped children naturally improve the coordination of the tongue, lips, jaw, and breathing mechanisms in an enjoyable learning environment. Three of the five children demonstrated significant improvement in articulation skills, while the remaining two showed gradual progress. The effectiveness of the stimulation was supported by teachers' consistency, a positive learning atmosphere, and parental involvement. In contrast, children's emotional conditions, individual developmental differences, and limited attention spans were identified as the main inhibiting factors. The study concludes that the Movement and Song of the Seven Habits of Great Indonesian Children is an effective, enjoyable, and contextual medium for improving articulation skills in early childhood.